Effects of Nitrogen Addition on Soil Carbon-Fixing Microbial Diversity on Different Slopes in a Degraded Alpine Meadow - Li, Chengyi; Li, Xilai; Shi, Yan; Yang, Yuanwu; Li, Honglin (Frontiers in Plant Science, 2022)
Autotrophic carbon-fixing bacteria are a major driver of carbon sequestration and elemental cycling in grassland ecosystems. The characteristics of the response of carbon-fixing bacterial communities to nitrogen (N) addition in degraded alpine meadows are unclear. In this study, it was investigated that the effects of N addition in three levels [they are low (LN), middle (MN), and high (HN) with N supplement of 2, 5, and 10 g N⋅m–2⋅a–1, respectively] on soil carbon-fixing bacteria on different slopes in a degraded alpine meadow in the Yellow River on the Qinghai–Tibet Plateau. The results showed that there were significant differences in the abundance of some low abundance genera of carbon-fixing bacteria on the same slope (P < 0.05), but the differences in the abundance of various phyla and dominant genera were not significant. MN on gentle slopes significantly reduced the Chao1 index and observed species (P < 0.05), whereas N addition on steep slopes had no significant effect on the diversity. The abundance of the Cyanobacteria phylum and 28 genera of identified carbon-fixing bacteria differed significantly between slopes (P < 0.05), and observed species of carbon-fixing bacteria were significantly higher on steep slopes than on gentle slopes (P < 0.05). Factors affecting the carbon-fixing bacteria community structure include slope, N addition, ammoniacal nitrogen (N-NH4+), microbial biomass carbon (MBC), soil water content (SWC), pH, soil C:N ratio, and microbial C:N ratio. Slope, N addition, soil physicochemical properties, microbial biomass, and stoichiometric ratio did not significantly affect the carbon-fixing bacteria diversity. Thus, the effect of exogenous N addition on carbon-fixing bacteria in degraded alpine meadows was dependent on slope conditions, and the response of carbon-fixing bacteria abundance and species number to N addition on gently slope sites was threshold-limited.